2012
DOI: 10.1089/ham.2012.1052
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 at the Blood-Brain Barrier: A Mediator of Permeability?

Abstract: The importance of the blood-brain barrier (BBB) in maintaining brain homeostasis cannot be better appreciated than during disease states, where disruption of its function is associated with dramatic detrimental clinical outcome. For decades, neuroscientists and neurobiologists investigated most neurological diseases under the prism of a neuro-centric view, considering the contribution of nonneural components of the CNS (BBB, choroid plexus) negligible or even irrelevant. However, recent reviews have highlighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 97 publications
(89 reference statements)
0
48
0
Order By: Relevance
“…The development and maintenance of these junctional proteins is dependent on a variety of proteins produced by astrocytes and pericytes. Hypoxia results in the release of hypoxia inducible factor-1 (HIF-1) [81,82]. In the presence of hypoxia, HIF-1 translocates from the cytoplasm to the nucleus where it binds to hypoxia-responsive elements resulting in the expression of a variety of genes involved in the adaptation to hypoxia.…”
Section: Hypoxia and The Blood Brain Barriermentioning
confidence: 99%
“…The development and maintenance of these junctional proteins is dependent on a variety of proteins produced by astrocytes and pericytes. Hypoxia results in the release of hypoxia inducible factor-1 (HIF-1) [81,82]. In the presence of hypoxia, HIF-1 translocates from the cytoplasm to the nucleus where it binds to hypoxia-responsive elements resulting in the expression of a variety of genes involved in the adaptation to hypoxia.…”
Section: Hypoxia and The Blood Brain Barriermentioning
confidence: 99%
“…These larger agents must, therefore, be regulated by transport proteins (e.g., GLUT1 for the passage of glucose) and by receptor-and adsorptive-mediated transcytosis (e.g., for insulin) (3)(4)(5). A range of physiological and pathological conditions readily alter transport across the BBB, including starvation (46), hypoxia (339) and heat stress (408). Indeed, BBB transport is far from static (207), while obvious consequences, including vasogenic edema, result from uncontrolled BBB opening.…”
Section: Quantifying Heat Illness and Heat Strokementioning
confidence: 99%
“…Two studies looked at the effects of chronic altitude exposure for at least 72 h (Li et al 2012;Helan et al 2014). Their outcomes are contradictory, Li et al (2012) showed a decrease in BDNF concentration after a 5-day acclimatization period at 3900 m, while Helan et al (2014) observed increased BDNF levels after 72 h at 3350 m. Both hypoxia and BDNF increased hypoxia-inducible factor 1 (Helan et al 2014), a factor that is considered as an important regulator in the hypoxic response of the BBB (Ogunshola and Al-Ahmad 2012). The discrepancy in these findings and the lack of effect on an acute exposure, as observed in the present study, elucidate the necessity for further research on the effects of altitude on BDNF, and the potential mechanisms involved.…”
Section: Cognitive Performance and Bdnfmentioning
confidence: 99%